1977
DOI: 10.1139/v77-032
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of metal hydrides. Part XX. The nature of the insertion rearrangement of acetylenes with platinum(II) hydrides

Abstract: . Can. J. Chem. 55, 189 (1977). The reactions of platinum(I1) hydrides, trans-PtHXL,, where X = NO3, Cl or CH,OH, and L = PEt, or tricyclohexylphosphine, with disubstituted acetylenes, R,C=CR,, have been examined under a variety of conditions. From spectroscopic parameters, the gross geometry at platinum as well as the geometry of the resulting alkenyl groups in the products have been determined. The observation that all alkenyl groups have a cis geometry is consistent with a migratory insertion step involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Each Pt is essentially square-planar coordinate in which the two σ-bound carbons are oriented cis to one another and each is trans to a coordinated π-bond. The stereochemistry about the terminal double bond of the tetraphenylbutadienyl ligand is trans.
4 ORTEP drawing of one of the two independent molecules in the asymmetric unit of 8 .
…”
Section: Resultsmentioning
confidence: 99%
“…Each Pt is essentially square-planar coordinate in which the two σ-bound carbons are oriented cis to one another and each is trans to a coordinated π-bond. The stereochemistry about the terminal double bond of the tetraphenylbutadienyl ligand is trans.
4 ORTEP drawing of one of the two independent molecules in the asymmetric unit of 8 .
…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the vinylic complexes derived from the cis addition of similar Pt hydrides to acetylenes often incorporated the more electron-withdrawing substituent of the acetylene on the α-carbon atom …”
Section: A Hydropalladation Of Alkynesmentioning
confidence: 99%
“…In contrast, the vinylic complexes derived from the cis addition of similar Pt hydrides to acetylenes often incorporated the more electron-withdrawing substituent of the acetylene on the R-carbon atom. 221 No firm conclusion was drawn regarding mechanisms of the Pd-H bond addition to the triple bond. However, it was demonstrated that the insertion occurred via an intermediate in which the hydrido ligand remained on the metal.…”
Section: A Hydropalladation Of Alkynesmentioning
confidence: 99%